Analysis of Food Security in Regional Context: West Java Provincial Government as a Case Study - Rudi Martiawan; Achdiat Achdiat; NR Ruyani; Ediyanto Ediyanto; Maun Jamaludin (LifeSciFi, 2023)
Food security in Indonesia is still experiencing problems, especially in the West Java region, starting from the problem of food availability and the ability of the community to meet food needs. The goal of food security is access for every household or individual to obtain food for the purposes of a healthy life with requirements for receiving food in accordance with prevailing values or culture by taking into account socio-economic conditions, access and availability of food. This study describes the condition of food security in the West Java Region as an implementation of food security policies issued by the Regional Government of West Java. This study uses a qualitative method. The data collected is sourced from primary and secondary data. The primary data comes from interviews with informants, including the heads of farmer groups, millers, rice and grain marketers and related agencies at the provincial level of West Java. Secondary data is sourced from the West Java Province Agriculture and Food Crops Office, the West Java Provincial Food Security Agency, and the West Java Regional Division of Bulog (Divre). The results of the study show that the food security policy of the West Java regional government in realizing food security has not made any significant changes to the yields of food crops obtained in West Java, even though the Regional Regulation of West Java Province No. Â 4 of 2012 concerning Regional Food Independence and other policies has been enacted in terms of food policy.